Non-therapeutic research in children. (June 2019) - May Ng, Sze
The future health of children depends on clinical research which is an important part of medical progress. The principles of the child's best interests standards and how it is applied in the context of research are explored. This review will show that there is a need for research involving children but there are gaps in the current legal and ethical framework which are not readily applicable to non-therapeutic research involving children. There are significant challenges in trying to achieve a balance between what is socially good and the obligation to protect children who participate in research.